Self-cleaning high-strength wear-resistant ceramic tile and preparation method thereof
By adding trans-4,4'-bis(dimethylamino)styrene, nanotitanium dioxide particles and nanosilica particles to the ceramic tiles, a photocatalytic-superhydrophobic composite system is formed, which solves the problems of insufficient self-cleaning, strength and wear resistance in high-pollution and high-wear environments, and achieves the overall performance improvement of the tiles.
Patent Information
- Application Number
- CN202411948689.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional ceramic tiles are difficult to achieve self-cleaning, high strength and wear resistance in high pollution and wear environments, and cannot meet the needs of modern buildings to improve the performance of ceramic tiles.
By adding trans-4,4'-bis(dimethylamino)styrene, nanotitanium dioxide particles and nanosilica particles, a photocatalytic-superhydrophobic composite system is formed to improve the self-cleaning ability of ceramic tiles, and through the reasonable proportioning and processing of a variety of inorganic materials, the strength and wear resistance of ceramic tiles are improved.
It realizes the self-cleaning effect of ceramic tiles in a highly polluted environment, significantly improves the strength and wear resistance of ceramic tiles, and can maintain long-term cleaning and overall performance in a high-wear environment.
Smart Images

Figure CN119751016A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a self-cleaning high-strength wear-resistant ceramic tile and a preparation method thereof. Background Art
[0002] With the development of modern construction industry, ceramic tiles, as an important material for indoor and outdoor decoration, have higher and higher performance requirements. Although traditional ceramic tiles have certain decorative and durability, they are still insufficient in self-cleaning, high strength and wear resistance. Especially in some highly polluted and highly abrasive environments, such as public places, industrial plants, and home kitchens, traditional ceramic tiles are prone to accumulate dust and stains, and the surface is easily worn after long-term use, affecting the appearance and service life.
[0003] A Chinese patent document with publication number CN107629650A provides a self-cleaning coating for a tile substrate, a preparation method and a use method thereof. The self-cleaning coating for a tile substrate comprises an intermediate layer and a self-cleaning layer. The intermediate layer is sprayed onto the tile substrate, and the self-cleaning layer is sprayed onto the intermediate layer. The intermediate layer comprises polyurethane, nano-silicon dioxide, nano-barium sulfate, sodium chloride, and toluene, and the self-cleaning layer comprises nano-titanium dioxide, sodium benzoate, water, calcite powder, and propylene glycol butyl ether.
[0004] However, firstly, the patent only provides a coating for realizing the self-cleaning function of ceramic tiles, and does not provide properties such as strength and wear resistance of ceramic tiles; secondly, the coating provided by the patent has a poor self-cleaning effect and cannot meet the use requirements in some high-pollution and high-wear environments, such as public places, industrial plants, and home kitchens.
[0005] In view of the above technical problems, the present invention proposes a self-cleaning, high-strength, wear-resistant ceramic tile and a preparation method thereof, so as to achieve a comprehensive improvement in the self-cleaning, high-strength and wear-resistant properties of the ceramic tile. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a self-cleaning high-strength wear-resistant ceramic tile and a preparation method thereof, which are as follows:
[0007] A self-cleaning high-strength wear-resistant ceramic tile comprises the following components by weight ratio: 30-35 parts of glass microbeads, 12-15 parts of hydroxyethyl methylcellulose, 8-10 parts of fly ash, 6-10 parts of bentonite, 5-8 parts of Bayer red mud, 7-9 parts of phosphogypsum, 4-7 parts of clay, 15-20 parts of mineralizer, 7-9 parts of alumina particles, 3-5 parts of quartz, 5-9 parts of titanium oxide, 2-4 parts of silicon oxide, 1-2 parts of yttrium oxide, 4-5 parts of potassium-sodium feldspar, 3-4 parts of zirconium silicate, 12-14 parts of barium carbonate, 10-12 parts of barium metaborate, 5-7 parts of barium sulfate, 11-15 parts of tetraethylene glycol dimethyl ether, 2-3 parts of nano titanium dioxide particles, 1-2 parts of nano silicon dioxide particles, and 0.5-0.8 parts of trans-4,4'-bis(dimethylamino)stilbene.
[0008] Preferably, a self-cleaning, high-strength, wear-resistant ceramic tile comprises the following ingredients, by mass ratio: 33 parts of glass beads, 13 parts of hydroxyethyl methylcellulose, 9 parts of fly ash, 8 parts of bentonite, 6 parts of Bayer red mud, 8 parts of phosphogypsum, 6 parts of clay, 17 parts of mineralizer, 8 parts of alumina particles, 4 parts of quartz, 7 parts of titanium oxide, 3 parts of silicon oxide, 1.5 parts of yttrium oxide, 4.5 parts of potassium and sodium feldspar, 3.5 parts of zirconium silicate, 13 parts of barium carbonate, 11 parts of barium metaborate, 6 parts of barium sulfate, 13 parts of tetraethylene glycol dimethyl ether, 2.5 parts of nano titanium dioxide particles, 1.5 parts of nano silicon dioxide particles, and 0.7 parts of trans-4,4'-bis(dimethylamino)stilbene.
[0009] Preferably, the mineralizer is calcium oxide.
[0010] The self-cleaning high-strength wear-resistant ceramic tile provided by the present invention is added with trans-4,4'-di(dimethylamino)stilbene, nano-titanium dioxide particles and nano-silicon dioxide particles with super-hydrophobic properties, which can form a highly efficient photocatalytic-super-hydrophobic composite system on the surface of the ceramic tile. Under light, trans-4,4'-di(dimethylamino)stilbene absorbs light energy and converts it into chemical energy, providing an electron source for the photocatalytic reaction of the nano-titanium dioxide, and the nano-titanium dioxide uses these electrons and holes to generate active oxygen species and strong oxidizing substances such as hydroxyl radicals to decompose and oxidize pollutants on the surface of the ceramic tile; at the same time, the super-hydrophobic layer prevents the attachment and deposition of water molecules and pollutants, further enhancing the self-cleaning ability of the ceramic tile; when trans-4,4'-di(dimethylamino)stilbene, nano-titanium dioxide particles and nano-silicon dioxide particles act together, the self-cleaning of the ceramic tile surface is completed together, further improving the self-cleaning function of the ceramic tile.
[0011] Preferably, the preparation method of the self-cleaning high-strength wear-resistant ceramic tile is as follows:
[0012] S1. Put glass microspheres, hydroxyethyl methyl cellulose, fly ash, bentonite, Bayer red mud and phosphogypsum into a grinder and grind to obtain primary particles;
[0013] S2, putting clay, mineralizer, alumina particles, quartz, titanium oxide, silicon oxide, yttrium oxide and potassium-sodium feldspar into a pulverizer for pulverization to obtain secondary particles;
[0014] S3, adding zirconium silicate, barium carbonate, barium metaborate, barium sulfate and tetraethylene glycol dimethyl ether into a reaction kettle and reacting for 15-18 minutes to obtain tertiary particles;
[0015] S4, dissolving trans-4,4'-di(dimethylamino)stilbene in ethanol to obtain a solution;
[0016] S5, mixing the primary particles obtained in S1, the secondary particles obtained in S2, and the tertiary particles obtained in S3, and stirring them evenly to obtain a ceramic tile precursor substrate;
[0017] S6, mixing the nano titanium dioxide particles and nano silicon dioxide particles with the primary particles obtained in S1, the secondary particles obtained in S2, the tertiary particles obtained in S3, and the solution obtained in S4, and stirring evenly to obtain a ceramic tile precursor surface material;
[0018] S7, mixing the ceramic tile precursor substrate obtained in S5 with clean water, stirring evenly, and then pressing and molding using a mold to obtain a ceramic tile substrate blank;
[0019] S8, then mix the ceramic tile precursor surface material obtained in S6 with clean water and apply it to the surface layer 4-6mm of the ceramic tile substrate blank obtained in S7 to obtain a ceramic tile blank; here, the ceramic tile precursor surface material can also be used as the whole raw material to be pressed into a ceramic tile blank. The double-layer blank is selected to save costs, and it can be selected according to needs in actual implementation;
[0020] S9, put the tile blank obtained in S8 into a kiln for firing to obtain self-cleaning high-strength wear-resistant tiles. Preferably, in step S1, the speed of the grinder is 6500-6600r / min, and the grinding time is 20-30 minutes.
[0021] Preferably, in step S1, the particle size of the primary particles is 50-80 μm.
[0022] Preferably, in step S2, the pulverizer is a jet pulverizer, and the pulverizing time is 2-5 minutes.
[0023] Preferably, in step S2, the particle size of the secondary particles is 30-50 μm.
[0024] Preferably, in step S3, the temperature of the reactor is 90°C-100°C and the rotation speed is 8500-9000 r / min.
[0025] Preferably, in step S3, the particle size of the tertiary particles is 40-60 μm.
[0026] Preferably, in step S7, the ceramic tile precursor substrate and clean water are mixed at a mass ratio of 3-5:1;
[0027] In the step S8, the ceramic tile precursor surface material is mixed with clean water at a mass ratio of 3-5:1.
[0028] Preferably, in step S9, the firing temperature of the tile blank in the kiln is 1720° C.-1780° C., and the firing time is 12-14 hours.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention can decompose organic pollutants under light conditions by adding nano titanium dioxide particles and nano silicon dioxide particles, so that the surface of the tile has an excellent self-cleaning effect; at the same time, the addition of trans-4,4'-di(dimethylamino)stilbene further enhances the photocatalytic activity and anti-aging performance of the tile, so that the tile can still remain clean in a long-term high-pollution environment.
[0031] 2. The trans-4,4'-di(dimethylamino)stilbene provided by the present invention is a stilbene-type photosensitizing dye, which can absorb light of a specific wavelength in sunlight or ultraviolet light and convert it into chemical energy or thermal energy. When combined with nano titanium dioxide particles, it can broaden the light absorption range of nano titanium dioxide and improve its light utilization rate. Under light, the dye molecules absorb light energy and then transition to an excited state to generate high-energy electrons. These high-energy electrons can be quickly transferred to the conduction band of nano titanium dioxide, providing the necessary electron source for the photocatalytic reaction of nano titanium dioxide. Nano titanium dioxide is a photocatalyst with excellent photocatalytic performance and chemical stability. Under light, nano titanium dioxide can generate photogenerated electrons and holes. These photogenerated electrons and holes have strong redox ability and can react with substances adsorbed on the catalyst surface. Specifically, the photogenerated electrons can react with oxygen molecules adsorbed on the surface of titanium dioxide to generate superoxide radicals (·O2 -) and other active oxygen species, which have strong oxidizing ability and can decompose organic matter, oxidize inorganic matter, and kill bacteria. At the same time, photogenerated holes can also react with water molecules or hydroxide ions adsorbed on the surface to generate strong oxidizing species such as hydroxyl radicals (·OH), which further participate in the degradation process of pollutants. The addition of trans-4,4'-bis(dimethylamino)stilbene can enhance the degradation process of pollutants by nano-titanium dioxide and improve the self-cleaning effect of tiles.
[0032] 3. The self-cleaning, high-strength, wear-resistant ceramic tile provided by the present invention is added with nano-silicon dioxide particles with super-hydrophobic properties, which can form a dense hydrophobic layer on the surface of the ceramic tile. This hydrophobic layer can reduce the surface energy of the ceramic tile surface, making it difficult for water molecules to spread on the surface, thereby reducing the adhesion and deposition of stains, grease and other pollutants on the ceramic tile surface. At the same time, the super-hydrophobic layer can also prevent water molecules from penetrating into the interior of the ceramic tile, further protecting the integrity and durability of the ceramic tile.
[0033] 4. The glass beads, fly ash, bentonite, Bayer red mud and other inorganic materials in the formula of the present invention have been reasonably proportioned and processed to form a compact and high-strength structure. The addition of hard materials such as alumina particles, quartz, and zirconium silicate further improves the hardness and wear resistance of the tiles, enabling them to withstand the use requirements in high-wear environments.
[0034] 5. The present invention utilizes industrial wastes such as fly ash and Bayer red mud as raw materials, which not only reduces production costs but also realizes the recycling of resources, which is in line with the concepts of green production and sustainable development.
[0035] 6. In view of the remarkable advantages of the ceramic tile of the present invention in self-cleaning, high strength and wear resistance, it is particularly suitable for some high-pollution and high-wear environments, such as public places, industrial plants, home kitchens, etc. These environments have extremely high performance requirements for ceramic tiles, and the ceramic tile of the present invention can meet these requirements well. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention is a flow chart for preparing the self-cleaning high-strength wear-resistant ceramic tile. DETAILED DESCRIPTION
[0037] Example 1
[0038] A self-cleaning high-strength wear-resistant ceramic tile comprises the following ingredients in proportion by mass: 30 parts of glass beads, 12 parts of hydroxyethyl methylcellulose, 8 parts of fly ash, 6 parts of bentonite, 5 parts of Bayer red mud, 7 parts of phosphogypsum, 4 parts of clay, 15 parts of mineralizer, 7 parts of aluminum oxide particles, 3 parts of quartz, 5 parts of titanium oxide, 2 parts of silicon oxide, 1 part of yttrium oxide, 4 parts of potassium-sodium feldspar, 3 parts of zirconium silicate, 12 parts of barium carbonate, 10 parts of barium metaborate, 5 parts of barium sulfate, 11 parts of tetraethylene glycol dimethyl ether, 2 parts of nano titanium dioxide particles, 1 part of nano silicon dioxide particles, and 0.5 part of trans-4,4'-bis(dimethylamino)stilbene.
[0039] Furthermore, the mineralizer is calcium oxide.
[0040] Moreover, if Figure 1 The preparation method of the self-cleaning high-strength wear-resistant ceramic tile is as follows:
[0041] S1. Put glass microspheres, hydroxyethyl methyl cellulose, fly ash, bentonite, Bayer red mud and phosphogypsum into a grinder and grind to obtain primary particles;
[0042] S2, putting clay, mineralizer, alumina particles, quartz, titanium oxide, silicon oxide, yttrium oxide and potassium-sodium feldspar into a pulverizer for pulverization to obtain secondary particles;
[0043] S3, adding zirconium silicate, barium carbonate, barium metaborate, barium sulfate and tetraethylene glycol dimethyl ether into a reaction kettle and reacting for 15-18 minutes to obtain tertiary particles;
[0044] S4, dissolving trans-4,4'-di(dimethylamino)stilbene in ethanol to obtain a solution;
[0045] S5, mixing the primary particles obtained in S1, the secondary particles obtained in S2, and the tertiary particles obtained in S3, and stirring them evenly to obtain a ceramic tile precursor substrate;
[0046] S6, mixing the nano titanium dioxide particles and nano silicon dioxide particles with the primary particles obtained in S1, the secondary particles obtained in S2, the tertiary particles obtained in S3, and the solution obtained in S4, and stirring evenly to obtain a ceramic tile precursor surface material;
[0047] S7, mixing the ceramic tile precursor substrate obtained in S5 with clean water, stirring evenly, and then pressing and molding using a mold to obtain a ceramic tile substrate blank;
[0048] S8, then mix the ceramic tile precursor surface material obtained in S6 with clean water and apply it to the surface layer of the ceramic tile substrate blank obtained in S7 to 4 mm, to obtain a ceramic tile blank;
[0049] S9, putting the tile blank obtained in S8 into a kiln for firing to obtain self-cleaning high-strength wear-resistant tiles.
[0050] Moreover, in the step S1, the rotation speed of the grinder is 6500 r / min, and the grinding time is 20 minutes.
[0051] Furthermore, in the step S1, the particle size of the primary particles is 50 μm.
[0052] Moreover, in the step S2, the pulverizer is a jet pulverizer, and the pulverizing time is 2 minutes.
[0053] Furthermore, in the step S2, the particle size of the secondary particles is 30 μm.
[0054] Furthermore, in step S3, the temperature of the reactor is 90° C. and the rotation speed is 8500 r / min.
[0055] Furthermore, in the step S3, the particle size of the tertiary particles is 40 μm.
[0056] Moreover, in the step S7, the ceramic tile precursor substrate and clean water are mixed at a mass ratio of 3:1;
[0057] In the step S8, the ceramic tile precursor surface material and clean water are mixed in a mass ratio of 3:1.
[0058] Moreover, in step S9, the firing temperature of the tile blank in the kiln is 1720° C. and the firing time is 12 hours.
[0059] Example 2
[0060] A self-cleaning high-strength wear-resistant ceramic tile comprises the following ingredients by weight: 30-35 parts of glass microbeads, 15 parts of hydroxyethyl methylcellulose, 10 parts of fly ash, 10 parts of bentonite, 8 parts of Bayer red mud, 9 parts of phosphogypsum, 7 parts of clay, 20 parts of mineralizer, 9 parts of alumina particles, 5 parts of quartz, 9 parts of titanium oxide, 4 parts of silicon oxide, 2 parts of yttrium oxide, 5 parts of potassium-sodium feldspar, 4 parts of zirconium silicate, 14 parts of barium carbonate, 12 parts of barium metaborate, 7 parts of barium sulfate, 15 parts of tetraethylene glycol dimethyl ether, 3 parts of nano titanium dioxide particles, 2 parts of nano silicon dioxide particles, and 0.8 parts of trans-4,4'-bis(dimethylamino)stilbene.
[0061] Moreover, if Figure 1 The preparation method of the self-cleaning high-strength wear-resistant ceramic tile is as follows:
[0062] S1. Put glass microspheres, hydroxyethyl methyl cellulose, fly ash, bentonite, Bayer red mud and phosphogypsum into a grinder and grind to obtain primary particles;
[0063] S2, putting clay, mineralizer, alumina particles, quartz, titanium oxide, silicon oxide, yttrium oxide and potassium-sodium feldspar into a pulverizer for pulverization to obtain secondary particles;
[0064] S3, adding zirconium silicate, barium carbonate, barium metaborate, barium sulfate and tetraethylene glycol dimethyl ether into a reaction kettle and reacting for 15-18 minutes to obtain tertiary particles;
[0065] S4, dissolving trans-4,4'-di(dimethylamino)stilbene in ethanol to obtain a solution;
[0066] S5, mixing the primary particles obtained in S1, the secondary particles obtained in S2, and the tertiary particles obtained in S3, and stirring them evenly to obtain a ceramic tile precursor substrate;
[0067] S6, mixing the nano titanium dioxide particles and nano silicon dioxide particles with the primary particles obtained in S1, the secondary particles obtained in S2, the tertiary particles obtained in S3, and the solution obtained in S4, and stirring evenly to obtain a ceramic tile precursor surface material;
[0068] S7, mixing the ceramic tile precursor substrate obtained in S5 with clean water, stirring evenly, and then pressing and molding using a mold to obtain a ceramic tile substrate blank;
[0069] S8, then mix the ceramic tile precursor surface material obtained in S6 with clean water and apply it to the surface layer of the ceramic tile substrate blank obtained in S7 to 6 mm, to obtain a ceramic tile blank;
[0070] S9, putting the tile blank obtained in S8 into a kiln for firing to obtain self-cleaning high-strength wear-resistant tiles.
[0071] Moreover, in the step S1, the rotation speed of the grinder is 6600 r / min, and the grinding time is 30 minutes.
[0072] Furthermore, in the step S1, the particle size of the primary particles is 80 μm.
[0073] Moreover, in the step S2, the pulverizer is a jet pulverizer, and the pulverizing time is 5 minutes.
[0074] Furthermore, in the step S2, the particle size of the secondary particles is 50 μm.
[0075] Furthermore, in step S3, the temperature of the reactor is 100° C. and the rotation speed is 9000 r / min.
[0076] Furthermore, in the step S3, the particle size of the tertiary particles is 60 μm.
[0077] Furthermore, in the step S7, the ceramic tile precursor substrate and clean water are mixed at a mass ratio of 5:1;
[0078] In step S8, the ceramic tile precursor surface material and clean water are mixed at a mass ratio of 5:1.
[0079] Moreover, in the step S9, the firing temperature of the tile blank in the kiln is 1780° C. and the firing time is 12-14 hours.
[0080] Example 3
[0081] A self-cleaning high-strength wear-resistant ceramic tile comprises the following ingredients by mass ratio: 33 parts of glass beads, 13 parts of hydroxyethyl methylcellulose, 9 parts of fly ash, 8 parts of bentonite, 6 parts of Bayer red mud, 8 parts of phosphogypsum, 6 parts of clay, 17 parts of mineralizer, 8 parts of aluminum oxide particles, 4 parts of quartz, 7 parts of titanium oxide, 3 parts of silicon oxide, 1.5 parts of yttrium oxide, 4.5 parts of potassium-sodium feldspar, 3.5 parts of zirconium silicate, 13 parts of barium carbonate, 11 parts of barium metaborate, 6 parts of barium sulfate, 13 parts of tetraethylene glycol dimethyl ether, 2.5 parts of nano titanium dioxide particles, 1.5 parts of nano silicon dioxide particles, and 0.7 part of trans-4,4'-bis(dimethylamino)stilbene.
[0082] Moreover, if Figure 1 The preparation method of the self-cleaning high-strength wear-resistant ceramic tile is as follows:
[0083] S1. Put glass microspheres, hydroxyethyl methyl cellulose, fly ash, bentonite, Bayer red mud and phosphogypsum into a grinder and grind to obtain primary particles;
[0084] S2, putting clay, mineralizer, alumina particles, quartz, titanium oxide, silicon oxide, yttrium oxide and potassium-sodium feldspar into a pulverizer for pulverization to obtain secondary particles;
[0085] S3, adding zirconium silicate, barium carbonate, barium metaborate, barium sulfate and tetraethylene glycol dimethyl ether into a reaction kettle and reacting for 15-18 minutes to obtain tertiary particles;
[0086] S4, dissolving trans-4,4'-di(dimethylamino)stilbene in ethanol to obtain a solution;
[0087] S5, mixing the primary particles obtained in S1, the secondary particles obtained in S2, and the tertiary particles obtained in S3, and stirring them evenly to obtain a ceramic tile precursor substrate;
[0088] S6, mixing the nano titanium dioxide particles and nano silicon dioxide particles with the primary particles obtained in S1, the secondary particles obtained in S2, the tertiary particles obtained in S3, and the solution obtained in S4, and stirring evenly to obtain a ceramic tile precursor surface material;
[0089] S7, mixing the ceramic tile precursor substrate obtained in S5 with clean water, stirring evenly, and then pressing and molding using a mold to obtain a ceramic tile substrate blank;
[0090] S8, then mix the ceramic tile precursor surface material obtained in S6 with clean water and apply it to the surface layer of the ceramic tile substrate blank obtained in S7 to 5 mm, to obtain a ceramic tile blank;
[0091] S9, putting the tile blank obtained in S8 into a kiln for firing to obtain self-cleaning high-strength wear-resistant tiles.
[0092] Moreover, in the step S1, the rotation speed of the grinder is 6650 r / min, and the grinding time is 25 minutes.
[0093] Furthermore, in the step S1, the particle size of the primary particles is 65 μm.
[0094] Moreover, in the step S2, the pulverizer is a jet pulverizer, and the pulverizing time is 3 minutes.
[0095] Furthermore, in the step S2, the particle size of the secondary particles is 40 μm.
[0096] Furthermore, in step S3, the temperature of the reactor is 95° C. and the rotation speed is 8700 r / min.
[0097] Furthermore, in the step S3, the particle size of the tertiary particles is 50 μm.
[0098] Furthermore, in the step S7, the ceramic tile precursor substrate and clean water are mixed at a mass ratio of 4:1;
[0099] In step S8, the ceramic tile precursor surface material and clean water are mixed in a mass ratio of 4:1.
[0100] Moreover, in step S9, the firing temperature of the tile blank in the kiln is 1750° C. and the firing time is 13 hours.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 3 is that no nano titanium dioxide particles are added.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 3 is that no nano silicon dioxide particles are added.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 3 is that no trans-4,4'-di(dimethylamino)stilbene is added, and the preparation method is as follows:
[0107] Moreover, if Figure 1 The preparation method of the self-cleaning high-strength wear-resistant ceramic tile is as follows:
[0108] S1. Put glass microspheres, hydroxyethyl methyl cellulose, fly ash, bentonite, Bayer red mud and phosphogypsum into a grinder and grind to obtain primary particles;
[0109] S2, putting clay, mineralizer, alumina particles, quartz, titanium oxide, silicon oxide, yttrium oxide and potassium-sodium feldspar into a pulverizer for pulverization to obtain secondary particles;
[0110] S3, adding zirconium silicate, barium carbonate, barium metaborate, barium sulfate and tetraethylene glycol dimethyl ether into a reaction kettle and reacting for 15-18 minutes to obtain tertiary particles;
[0111] S4, mixing the primary particles obtained in S1, the secondary particles obtained in S2, and the tertiary particles obtained in S3, and stirring them evenly to obtain a ceramic tile precursor substrate;
[0112] S5, mixing the nano titanium dioxide particles, nano silicon dioxide particles, the primary particles obtained in S1, the secondary particles obtained in S2, and the tertiary particles obtained in S3, and obtaining a ceramic tile precursor surface material;
[0113] S6, mixing the ceramic tile precursor substrate obtained in S4 with clean water, stirring evenly, and then pressing and molding using a mold to obtain a ceramic tile substrate blank;
[0114] S7, then mix the ceramic tile precursor surface material obtained in S6 with clean water and apply it to the surface layer of the ceramic tile substrate blank obtained in S6 to 4-6 mm to form a whole, thereby obtaining a ceramic tile blank;
[0115] S8, putting the tile blank obtained in S7 into a kiln for firing to obtain self-cleaning high-strength wear-resistant tiles.
[0116] Comparative Example 4
[0117] The difference between this comparative example and Example 3 is that trans-4,4'-di(dimethylamino)diphenyl is replaced by other common photosensitizing dye: rhodamine B.
[0118] Experimental Section
[0119] Experimental Grouping
[0120] Group A: tiles prepared in Example 1;
[0121] Group B: tiles prepared in Example 2;
[0122] Group C: tiles prepared in Example 3;
[0123] Group D: ceramic tile prepared in Comparative Example 1 (without addition of nano titanium dioxide particles);
[0124] Group E: tiles prepared in Comparative Example 2 (without the addition of nano-silica particles);
[0125] Group F: tiles prepared in Comparative Example 3 (without addition of trans-4,4'-bis(dimethylamino)stilbene);
[0126] Group G: tiles prepared in Comparative Example 4 (trans-4,4'-bis(dimethylamino)stilbene was replaced by rhodamine B);
[0127] Group H: Commercially available marble tiles (thickness consistent with other groups).
[0128] 1. Wear resistance test:
[0129] 1. Randomly select one tile from each of the above groups as a test sample, clean and dry the sample to remove stains and moisture on the surface.
[0130] 2. Use an electronic balance to accurately measure the initial mass of each sample and record the data.
[0131] 3. Place the sample on a wear tester, set an aqueous solution containing 0.5% sand as the wear medium, wear it once per second, for a total of 10,000 times, and start the tester to simulate wear.
[0132] 4. After the wear test, use the electronic balance to measure the mass of each sample again and record the data.
[0133] The mass loss of each sample, that is, the mass difference before and after wear, was calculated, as shown in Table 1 below.
[0134] Table 1 Wear resistance test results
[0135]
[0136]
[0137] As can be seen from Table 1, the tiles prepared in the embodiments of the present invention and comparative examples 1-4 have a mass loss of 0.22g-0.38g, and their wear resistance is significantly better than that of the commercially available marble tiles (group H). Among the test samples in group AG, the mass loss of the tiles prepared in embodiments 1-3 (groups A, B, and C) is significantly lower than that of the tiles prepared in comparative examples 1-4 (groups D, E, F, and G), which proves that the tiles prepared in the present invention have a significant wear resistance effect. Among the samples in groups A, B, and C, group B has the best effect, with a mass loss of only 0.22g.
[0138] 2. Strength test:
[0139] 1. Randomly select a tile from each group as the test sample and place the tile sample on the table of the press to ensure that the sample is centered and stable.
[0140] 2. Place the pressure gauge in the center of the tile sample and make sure that the measuring head of the pressure gauge is in good contact with the surface of the tile sample.
[0141] 3. Place a steel ball with a diameter of 10mm on the pressure gauge head to better disperse the pressure and measure the compressive strength of the tile.
[0142] 4. Start the press, slowly lower the pressure head until it contacts the surface of the steel ball and gradually apply pressure, so that the pressure head gradually applies vertical pressure to the tile sample. When the pressure value stabilizes, record the value as the stable pressure of the tile sample under pressure (Table 2).
[0143] 5. Continue to apply pressure until the tile sample breaks, and record the maximum pressure value at the time of rupture (Table 2).
[0144] Table 2 Strength test results
[0145] Group Stable pressure (MPa) Maximum pressure at rupture (MPa) A 46.23 697.45 B 47.12 702.89 C 46.87 695.32 D 44.98 678.54 E 45.31 684.17 F 45.02 680.76 G 44.78 675.93 H 42.34 620.15
[0146] As can be seen from Table 2, the tiles prepared in Examples 1-3 (Groups A, B, and C) and Comparative Examples 1-4 (Groups D, E, F, and G) all exhibited higher values in terms of stable pressure and maximum pressure at rupture, which were better than Group H (commercially available marble tiles), while the stable pressure and maximum pressure at rupture of Groups A, B, and C were higher than those of Groups D, E, F, and G, with Group B having the best effect.
[0147] The stable pressure of tiles under pressure reflects their pressure-bearing capacity, that is, within a certain period of time, the tiles can withstand and maintain a stable maximum vertical pressure without significant deformation or damage. It is used to measure the durability and load-bearing capacity of tiles. High stable pressure means that the tiles can better withstand the pressure from furniture, human activities or other heavy objects during long-term use, and are not prone to dents, cracks and other problems, thereby extending their service life. The maximum pressure when the tile breaks directly reflects its compressive strength, that is, the maximum pressure value that the tile can withstand when subjected to vertical pressure until it breaks. It is an important indicator for measuring the crack resistance and overall strength of the tile. A high rupture pressure value indicates that the tile has a stronger crack resistance and higher overall strength, and can maintain integrity under extreme conditions (such as heavy object impact, ground subsidence, etc.), reducing safety hazards and maintenance costs caused by rupture.
[0148] This experiment evaluated the pressure-bearing capacity and crack resistance of the tiles by recording and analyzing the stable pressure of the tiles and the maximum pressure when they broke. It was proved that the tiles prepared by the present invention have good compressive strength, durability and load-bearing capacity, and have significant advantages in strength.
[0149] 3. Self-cleaning ability test:
[0150] 1. Randomly select four tiles from each group as test samples, place each group of tile samples under the same conditions, and evenly apply ink, coffee, red wine, and oil on the tile surface.
[0151] 2. Keep it for 24 hours to ensure that the stains fully penetrate the surface of the tile.
[0152] 3. Use detergent to clean the above tiles and drain the water.
[0153] 4. Carefully observe the residual stains on the surface of the tiles. The results are shown in Table 3.
[0154] Table 3 Self-cleaning ability test results
[0155]
[0156]
[0157] As can be seen from Table 3, the tiles prepared in Examples 1-3 (Groups A, B, and C) have no or slight stains left after cleaning, and perform well to excellent in the stain resistance test; the tiles prepared in Comparative Examples 1-4 (Groups D, E, F, and G) have obvious or even serious stains left, and perform average or poor in the stain resistance test, especially for stains such as ink and red wine, and have poor cleaning ability; the tiles in Group H have only good cleaning effects on oil stains, and perform poorly for other stains. In summary, it can be proved that the self-cleaning high-strength wear-resistant tiles provided by the present invention are better than the comparative examples and commercially available marble tiles in terms of wear resistance, strength, and self-cleaning ability.
Claims
1. A self-cleaning high-strength wear-resistant tile, characterized in that: The composition is composed of the following ingredients by mass ratio: 30-35 parts of glass beads, 12-15 parts of hydroxyethyl methyl cellulose, 8-10 parts of fly ash, 6-10 parts of bentonite, 5-8 parts of Bayer red mud, 7-9 parts of phosphogypsum, 4-7 parts of clay, 15-20 parts of mineralizer, 7-9 parts of alumina particles, 3-5 parts of quartz, 5-9 parts of titanium oxide, 2-4 parts of silicon oxide, 1-2 parts of yttrium oxide, 4-5 parts of potassium-sodium feldspar, 3-4 parts of zirconium silicate, 12-14 parts of barium carbonate, 10-12 parts of barium metaborate, 5-7 parts of barium sulfate, 11-15 parts of tetraethylene glycol dimethyl ether, 2-3 parts of nano titanium dioxide particles, 1-2 parts of nano silicon dioxide particles and 0.5-0.8 parts of trans-4,4'-bis(dimethylamino)stilbene.
2. A self-cleaning high-strength wear-resistant ceramic tile as claimed in claim 1, characterized in that: The preparation method of the self-cleaning high-strength wear-resistant ceramic tile is as follows: S1. Put glass microspheres, hydroxyethyl methyl cellulose, fly ash, bentonite, Bayer red mud and phosphogypsum into a grinder and grind to obtain primary particles; S2, putting clay, mineralizer, alumina particles, quartz, titanium oxide, silicon oxide, yttrium oxide and potassium-sodium feldspar into a pulverizer for pulverization to obtain secondary particles; S3, adding zirconium silicate, barium carbonate, barium metaborate, barium sulfate and tetraethylene glycol dimethyl ether into a reaction kettle and reacting for 15-18 minutes to obtain tertiary particles; S4, dissolving trans-4,4'-di(dimethylamino)stilbene in ethanol to obtain a solution; S5, mixing the primary particles obtained in step S1, the secondary particles obtained in step S2, and the tertiary particles obtained in step S3, and stirring them evenly to obtain a ceramic tile precursor substrate; S6, mixing the nano titanium dioxide particles and nano silicon dioxide particles with the primary particles obtained in step S1, the secondary particles obtained in step S2, the tertiary particles obtained in step S3, and the dissolved solution obtained in step S4, and stirring evenly to obtain a ceramic tile precursor surface material; S7, mixing the ceramic tile precursor substrate obtained in step S5 with clean water, stirring evenly, and then pressing and molding using a mold to obtain a ceramic tile substrate blank; S8, then mixing the ceramic tile precursor surface material obtained in step S6 with clean water and applying it to the surface layer 4-6 mm of the ceramic tile substrate blank obtained in step S7 to obtain a ceramic tile blank; S9, placing the tile blank obtained in step S8 into a kiln for firing to obtain self-cleaning high-strength wear-resistant tiles.
3. A self-cleaning high-strength wear-resistant ceramic tile as claimed in claim 2, characterized in that: In step S1, the rotation speed of the grinder is 6500-6600 r / min, and the grinding time is 20-30 minutes.
4. A self-cleaning high-strength wear-resistant ceramic tile as claimed in claim 3, characterized in that: In the step S1, the particle size of the primary particles is 50-80 μm.
5. The self-cleaning high-strength wear-resistant ceramic tile according to claim 2, characterized in that: In the step S2, the pulverizer is a jet pulverizer, and the pulverizing time is 2-5 minutes.
6. A self-cleaning high-strength wear-resistant ceramic tile as claimed in claim 5, characterized in that: In the step S2, the particle size of the secondary particles is 30-50 μm.
7. The self-cleaning high-strength wear-resistant ceramic tile according to claim 2, characterized in that: In step S3, the temperature of the reactor is 90°C-100°C and the rotation speed is 8500-9000r / min.
8. A self-cleaning high-strength wear-resistant ceramic tile as claimed in claim 7, characterized in that: In the step S3, the particle size of the tertiary particles is 40-60 μm.
9. The self-cleaning high-strength wear-resistant ceramic tile according to claim 2, characterized in that: In the step S7, the ceramic tile precursor substrate and clean water are mixed at a mass ratio of 3-5:1; In step S8, the ceramic tile precursor surface material and clean water are mixed at a mass ratio of 3-5:
1.
10. The self-cleaning high-strength wear-resistant ceramic tile according to claim 2, characterized in that: In step S9, the firing temperature of the tile blank in the kiln is 1720° C.-1780° C., and the firing time is 12-14 hours.
Citation Information
Patent Citations
Self-cleaning paint used for tile substrate, preparation method and usage method thereof
CN107629650A
Cited By
Golden velvet texture easy-to-clean anti-skid ceramic tile and preparation process thereof
CN121021198A